AIRO GORTEC consensus on postoperative radiotherapy (PORT) in low-intermediate risk early stages oral squamous cell cancers (OSCC). (December 2022) - Merlotti, Anna; Alterio, Daniela; Orlandi, Ester; Racadot, Séverine; Bonomo, Pierluigi; Franco, Pierfrancesco; D'Angelo, Elisa; Ursino, Stefano; Pointreau, Yoann; Lapeyre, Michel; Graff, Pierre; Di Rito, Alessia; et al.
Highlights: Evidence on the efficacy of postoperative radiotherapy (PORT) in low\intermediate-risk squamous cell carcinoma of the oral cavity (OSCC) remains inconclusive. Members of a task force from two national radio-oncology Associations (AIRO and GORTEC) assessed experts' consensus among radiation oncologists for PORT indications in this subset of patients. fourteen statements were voted on and received an agreement. suggestions provided by experts in the field could help the decision-making process in some clinical scenarios. This document is intended to support and not replace the multidisciplinary discussion, which remains a fundamental step in all cases. Abstract: Evidence on the efficacy of postoperative radiotherapy (PORT) in low-intermediate risk squamous cell carcinoma of the oral cavity (OSCC) remains inconclusive. Members of a task force from two national radio-oncology Associations (AIRO and GORTEC) defined 14 clinically relevant questions to identify "gray areas" pertinent to the indication for PORT in this clinical setting. Consequently, a literature review was performed on the topic. The resulting statements were then rated by an Expert Panel (EP) using a modified Delphi method. Only radiation oncologists were part of the discussion and voting on the scenarios. There was agreement on the 14 statements at the first round of voting. The task force then decided to propose clinical cases for the two more controversial statements that had received a lower agreement to better capture the Experts' attitudes. The clinical cases highlighted a more significant decisional heterogeneity. However, the good level of consensus reached among the two Associations gives relevant support in informing clinical choices while acknowledging general indications cannot fit all clinical situations and do not replace multidisciplinary discussion.